Optimization of a Polarization-Encoding System for Practical Quantum Key Distribution - Costa, Hugo F.; Muga, Nelson J.; Silva, Nuno A.; Pinto, Armando N. (Anais do Workshop de Comunicação e Computação Quântica (WQuantum); 2022: Anais do II Workshop de Comunicação e Computação QuânticaDO - 10.5753/wquantum.2022.223949, 2022)
We present a method for optimizing the waveplate’s voltage range of an electro-optic based electrical polarization controller for qubit encoding in discrete-variable quantum key distribution (QKD). By increasing the number of used waveplates, the maximum voltage range to generate each of the states-of-polarization required by a QKD protocol can be reduced. The proposed machine learning algorithm, particle swarm optimization, was validated through numerical and experimental results. Results show that transitions between six states of polarization used in QKD systems can be generated using a maximum voltage range of 10V in each waveplate.